Two new species of Hymenochaete (Hymenochaetaceae, Basidiomycota) and H. colliculosa new to China from Shanxi Province - He, Shuang-Hui; Liu, Shi-Liang; Li, Hai-Jiao; Dai, Yu-Cheng (Phytotaxa, 2017)
Hymenochaete angustispora and H. verruculosa spp. nov. are described and illustrated from Shanxi Province, northern China. Hymenochaete angustispora was collected on Vitex negundo, and is characterized by resupinate basidiocarps, the absence of a hyphal layer, and narrowly cylindrical to allantoid basidiospores 5–7 × 1.8–2.2 µm. Hymenochaete verruculosa was collected on Cornus sp., and is distinct by the effuso-reflexed basidiocarps with a verruculose hymenophore, the presence of a cortex and hyphal layer, and small ellipsoid basidiospores 3.5–4.5 × 2–2.8 µm. Hymenochaete colliculosa, collected on Berberis sp., is reported in China for the first time. The phylogeny of 57 Hymenochaete species was inferred from a concatenated dataset of nuc rDNA ITS1-5.8S-ITS2 (ITS barcode) and D1-D2 domains of nuc 28S rDNA (28S) sequences.